(untitled) (Malay Literature, 2014)
Accepting that there is a close connection between religion and poetry, the paper focuses on the person that is presented in poetry in Malay in response to the Divine. The concept of "the person" used contains three elements: (a) the human identity - our common physiological and psychological qualities; (b) the social identity - arising from our membership in the various groups that make up our particular society; and, (c) the self - the unique personal sense of who I am. It argues that the person in Malay religious poetry is largely a "social identity" the self surrendered to God through membership in the Muslim community. Keywords: religious poetry, person, human identity, social identity, the individual self